Ante pacem: archaeological evidence of church life before Constantine - Snyder, Graydon F. (Mercer University Press, 2018)
Early Christianity emerged from obscurity to dominate the Roman world: that story, told and retold, continues to fascinate historians and believers. But the religion of ordinary Christians is not so well or easily known; they have left us no literary record of their faith and their hope, their marrying and their dying, their worship and their common life. Before the publication of "Ante Pacem there was no introduction or source-book for early Christian archaeology available in English. With his book Professor Snyder has performed an incalculable service for students of early Christianity and the world of late antiquity. He analyzes in one lavishly illustrated volume every piece of evidence that can, with some degree of assurance, be dated before the triumph of the emperor Constantine at the Milvian Bridge in 312CE thrust the nascent Christian culture "into a universal role as the formal religious expression of the Roman Empire."